ANALISIS PENDAPATAN DAN EFISIENSI TEKNIS USAHATANI BAWANG MERAH DI KECAMATAN GUNUNG ALIP KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Imelda Pratiwi Putri; Bustanul Arifin; Ktut Murniati (Lampung University, 2021)
Shallots are one of the unsubstituted agricultural commodities. The author is drawn to the onion commodity because of the many public complaints related to fluctuations in the price of shallots and their limited availability, especially on religious holidays and year-end. In addition, the availability of production factors is also often complained by farmers. Gunung Alip District is one of the districts that has the largest onion production in Tanggamus District, but its productivity is lower than that in other districts. The purpose of this study was to analyze agricultural income and technical efficiency of shallot farming in third season in Gunung Alip district, Tanggamus district. Data collection was carried out from March to April 2019. The research location was in Gunung Alip Subdistrict with the consideration that Gunung Alip Subdistrict is the area that has the largest area of harvest and onion production in Tanggamus Regency. Data collection was carried out using a questionnaire. Sampling is done by census method because all populations are sampled. The results stated that the onion farming was technically efficient. Income from cash costs and total costs obtained by farmers is IDR65,150,679.27 and IDR56,773,414.27 per hectare with R/C over cash costs 2.60 and R/C over total costs 2.16.Key words: income, technical efficiency, shallots farming